(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Sciatica is pain or paraesthesia which is radiates path of the sciatic nerve and its branches from the lower back through the hips and buttocks and down to the leg. A 41-year-old female patient with an acute low back ache to radiate to left lower limb with paraesthesia for three months came to Kayachikitsa IPD of Vaidyaratnam Ayurveda College on 18/3/24. The pain was graded eight out of ten in the VAS pain scale and her overall Oswestry low back pain score is 32 which means severe functional disability. She underwent for Vatakapha hara chikitsa protocol. It includes Rookshana, Snigda sweda, Vata hara, and Brihmana chikitsa. Ayurvedic preparations like Aadarisahacharadi kasayam, Suntibaladi choornam Vyoshadi guggulu were given Swedam, Patrapoliswedam, and Pizhichil, Shastika pinda swedam, Yoga vasti along with passive exercise were given. After 30 days of treatment outcome of these treatments found to be very positive. There was a substantial recovery in walking duration, heaviness, touch temperature perception and pain relief was observed. Subjective parameters like, SLR test, Oswestry low back pain disability questionnaire, Sciatica bothersome index, Sciatica frequency index, Roland morris low back pain and disability questionnaire was taken for assessment parameters. The patient got relief in all parameters after treatment. It was proved significant improvement of patient’s primary symptoms. These therapies reduce pain, stiffness and improve circulation.